Percutaneous Transluminal Angioplasty of Subclavian Artery Lesions - Jahic, Elmir (Med Arch, 2019)
INTRODUCTION: Percutaneous transluminal angioplasty (PTA) is one of the treatment options for stenotic and obstructive lesions of the subclavian artery. AIM: To evaluate initial and long-term results of percutaneous transluminal angioplasty of subclavian artery lesions. METHODS: During period February 2016 to December 2017, 26 patients (12 men and 14 women) with significant subclavian artery stenosis and occlusion were admitted and underwent PTA. All patients were symptomatic. All PTA procedures were performed with the patient under local anesthesia, through the femoral artery (n=22), brachial artery (n=4), or combined route (n=6). In 7 patients, we performed direct stenting, while in the other 15 patients we performed predilatation before stent implantation. The follow-up protocol consisted of regular clinical examinations in 1, 3, 6 and 12 months post-procedural, and annually thereafter with duplex ultrasound monitoring. RESULTS: Initial technical success was achieved in 22 of 26 procedures (84.61%), 100% in stenotic lesions and 55.5 % in total occlusions. Fourth of nine occlusions could not be recanalized by PTA. These patients were managed surgically. The 30-day mortality rate was 0% for the entire group. No patients required reintervention for recurrence of symptoms and the stents remain patent at period of 12 months post-procedural. CONCLUSION: The minimal invasive technique, the markedly lower complication rate, the high long-term patency, patient’s comfort and the decreased hospital stay have made endovascular repair the primary choice of treatment in the majority of cases, especially in patients with stenotic lesions and high-risk patients. We consider PTA of subclavian artery stenotic/obstructive lesions should be the first therapeutic option.